Lithostratigraphic and structural reconstruction of the Zn-Pb-Cu-Ag-Au Lemarchant volcanogenic massive sulphide (VMS) deposit, Tally Pond group, central Newfoundland, Canada - Cloutier, Jonathan; Piercey, Stephen J.; Lode, Stefanie; Vande Gutche, Michael; Copeland, David A. (Ore Geology Reviews, 2018)
Financial support for this project was provided from a Natural Sciences and Engineering Research Council of Canada (NSERC) Collaborative Research and Development Grant to S.J. Piercey. Additional funding was provided by the NSERC-Altius Industrial Research Chair in Mineral Deposits (supported by NSERC, Altius Resources Inc., and the Research and Development Corporation of Newfoundland and Labrador) and an NSERC Discovery Grant to S.J. Piercey. The Lemarchant volcanogenic massive sulphide (VMS) deposit (1.24 Mt grading at 0.58% Cu, 5.38% Zn, 1.19% Pb, 1.01g/t Au, and 59.17g/t Ag) is a bimodal-felsic VMS deposit hosted within the Late Cambrian ($513–509 Ma) Tally Pond group of the Exploit Subzone in central Newfoundland, Canada. The deposit is hosted by andesitic volcaniclastic and volcanic rocks with subordinate dacite flows. The mineralisation is hosted by the dacites and is overlain by pillowed and massive basalts.Four structural breaks offset the local stratigraphic sequences including: 1) the LJ syn-volcanic shear zone; 2) the KJ syn-volcanic shear zone; 3) the Lemarchant thrust; and 4) the Bam normal fault. Deformation of the Lemarchant likely occurred during the Penobscot orogeny (486–478 Ma). Early deformation is marked with the local deformation of the LJ and KJ syn-volcanic shear zones during NW-SE compression which coincided with the development of the Lemarchant thrust. A late (<465Ma) east trending normal fault, the Bam fault, affected the central portion of the Lemarchant area and down-faulted the southern portion of the study area relative to the northern portion.Immobile element systematics of all the sequences from the Lemarchant deposit are tholeiitic with transitional Zr/Y ratios (1.9–6.6), Lan/Smn ratios <1 (normalised to upper crust), and have primitive mantle extended rare earth elements profiles with slight light rare earth element (LREE)-enriched pat- terns with flat heavy REE (HREE), and weak to strong negative Nb, Zr, and Ti anomalies. Together, these geochemical features, coupled ...